CORRELATION OF THIGH RHEOVASOGRAPHIC INDICES WITH CONSTITUTIONAL CHARACTERISTICS IN VOLLEYBALL PLAYERS OF ECTO-MESOMORPHIC SOMATOTYPE - Moroz, V.M.; Khapitska, O.P.; Sarafinyuk, L.A.; Iaremyn, S.Y.; Аndroshchuk О.V. (World of Medicine and Biology, 2019)
It has been established that volleyball players with ecto- mesomorphic somatotype have numerous statistically significant correlations between the parameters of the thigh rheovasogram and anthropometric and somatotypological indices. The most numerous and strongest correlations has been found between the indices of the external composition of the body, in particular, longitudinal, transverse, circumferential dimensions, thickness of the skin and fat folds, somatotypological characteristics and temporal, amplitude parameters of the rheogram, hemodynamic indices and arterial tone indices, with predominant direct moderate and strong correlations.